Isolement et caractérisation des rhizobactéries d’intérêt biotechnologique - BENCHAIB, Fatima Zohra; HACHI, Meriem (My University, 2021)
Indole acetic acid is an important auxin produced by growth-promoting rhizobacteria, the objective of this study is the amelioration of IAA production by bacterial strains isolated from the soil.Thirty-one strains were isolated from six soil samples (from the communes of Hadjadj and Masra in the wilaya of Mostaganem).The detection of IAA is based on a colorimetric reaction.twenty one strains were found to have the capacity to produce auxin. The amounts of auxin produced ranged from 3.07±0.021 to 55.74±0.028 μg/ml . E2 is the best producer with a value of 55.74±0.028 μg/ml PS.
Keywords: PGPR , Indole acetic acid , auxin